Dynamic condylar screws versus 95º angle blade plate fixation of subtrochantric fractures of femur - Vashisht, Deepak; Sreen, Sanjeev; Daroch, Manjit S.; Alawadhi, Karan (International Journal of Research in Medical Sciences, 2017)
Background: The purpose of this prospective randomized study was to evaluate the results of dynamic condylar screw (DCS) system and 95º angle blade plate fixation in the management of sub-trochanteric femoral fractures, regarding stability, union time, complication rate and functional out come. Methods: Total 30 consecutive patients with sub-trochanteric fracture were studied. The inclusion criteria were closed sub-trochanteric fractures in adults of both gender aged 18 years or above. Pathological fractures and open fractures were excluded from the study. After fixation of fractures with dynamic condylar screw system and 95º angle blade plate patients were followed up in OPD at an interval of 2 weeks till full weight bearing was started and then after at an interval of 4 weeks. Results of treatment were assessed by the Harris hip score for clinical and radiological assessment at the end of 6 months. Results: Among 30 studied cases, males were 22 (73.30%) and female 8 (26.70%). Most common mode of injury was road traffic accidents that occurred in 17 patients (56.70%) and the rest 13 patients had a history of fall. Patients were divided into two random groups (A &B) of 15 cases each. Group A was treated with DCS and Group B was treated with Angle Blade Plate 95º implants. Radiological union in most of the patients (13 out of 15 cases) treated with 95°angle blade plate occurred between 14-18 weeks, while in cases treated with dynamic condylar screw radiological union in most of the patients (14 out of 15) occurred between 12-16 weeks. According to Harris hip score, good to excellent results were achieved in 10 cases (66.66%) of 95°angle blade plate group and 14 cases (93.33%) of dynamic condylar screw group. Conclusions: Patients with sub-trochanteric fractures treated with dynamic condylar screw had earlier radiological union, better functional outcome, less complications and earlier weight bearing.